(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Fahr’s disease is a rare neurodegenerative disorder characterized by abnormal brain calcifications, typically presented in middle age. This case report describes an unusual presentation in a 14-year-old boy, highlighting the importance of considering Fahr’s disease in pediatric patients. The patient had a 5-year history of seizures, cognitive decline, and behavioral disturbances, along with obesity, short stature, low intelligence, and a clumsy gait. Imaging revealed extensive symmetrical calcifications in the basal ganglia, dentate nucleus, and cerebral white matter, confirming Fahr’s disease. The condition can present diverse neurological and psychiatric symptoms, including seizures, movement disorders, cognitive impairment, and mood disturbances. Diagnosis requires excluding secondary causes of brain calcification and is supported by characteristic radiological findings and the absence of biochemical abnormalities. This case underscores the need for early recognition and comprehensive evaluation to optimize management and improve the patient’s quality of life, even in the absence of family history. J Bangladesh Coll Phys Surg 2025; 43: 183-185